GRP-032 Beneficial Effect of Hospital Pharmacist Participation in Intensive Care Rounds: Reduction in Medicines Errors and Hospital Costs. (12th March 2013) - Goede, AL de; Bemt, PMLA van den; Becker, ML; Bommel, J van; Hunfeld, NGM
Abstract : Background: Medicines errors may result in patient harm. Especially in intensive care patients, adverse drug events caused by medicines errors are common. Interventions by hospital pharmacists have been shown to reduce adverse drug events and costs in intensive care units (ICUs). Purpose: To evaluate the effect of active participation of a hospital pharmacist in the ICU on medicines errors and hospital costs. Materials and Methods: A three-month pilot study was performed at the adult 32-bed ICU of the academic hospital Erasmus MC. Four hospital pharmacists were trained in specific aspects and protocols of intensive care. From July to September 2011, each patient's medicines profile was reviewed weekly using a standardised written form and a pharmacist was present on rounds. Potential medicines errors requiring intervention were documented and discussed during the round. In addition, the amount of time spent performing clinical activities at the ICU was recorded. Results: 267 medicines reviews were performed for a total of 169 patients in 51 rounds. 288 interventions for a total of 120 drugs were made. About 60% of the medicines reviews resulted in at least one intervention with an acceptance rate of 56%. Non-acceptance was mainly due to a lack of information at the time the medicines review was performed. 30% of interventions were relating to unnecessary drug use, 24% to drug omission and 17% to a wrong dose. Time spent on medicines reviews and visiting rounds was 7.3 hour per week. Based on these results we developed a business case for structural participation of a hospital pharmacist at the ICU. Conclusions: Participation of a hospital pharmacist in ICU rounds improves medicines safety and can be cost-effective. The pilot study and business case have resulted in the appointment of 0.5 FTE hospital pharmacist in the ICU. No conflict of interest.